Pengaruh Kesadaran Diri atas Kebutuhan dan Motivasi Terhadap Keputusan Pembelian Konsumen (Studi Kasus pada Pengguna PC Tablet Samsung Galaxy Tab di Bogor) - Krisnayakti, Denni; ., Sujana (LPPM Institut Bisnis dan Informatika Kesatuan, 2017)
This research is motivated by the competitions in the field of advance technology between two vendors of mobile device, Apple and Samsung. Both have become world’s largest chip buyers during 2013. In 2012, Samsung’s Galaxy Tab experienced a notable 4 times increase in its sales world wide compared to previous year, and in Indonesia alone, Galaxy Tab has defeated the sales of Apple’s Ipad. The research is aimed to discover the influence of customers’ self awareness of the needs and motivations on buying decision. The study is conducted on users or owners of Samsung’s Galaxy Tab is Bogor, and acquired 100 respondents using sampling methods. Method of analysis used is quantitative, and all data have fulfilled validity, reliability and classical assumption tests. The variables are buying decision (X), self awareness (X1), and motivation (X2). Hipotheses tested using t-test show that both independent variables observed are positively proven of having influence on dependent variables of buying decision. Then using F test we learn that both variables are suitable to test the dependent variables of buying decisions. Reliability test value is 0.699 which is greater than 0.6 and the classical assumption test acquired show that the data is normal, and after the normality test where the Skewness and Kurtosis value is between -2 and 2. There is no heteroskedasticity, and no multicolinearity becaue VIF value smaller than 10.